Management of Scheuermann’s Disease: A Literature Review - Pielusiński, Kamil Tomasz; Olejnik, Michał; Swoboda, Kamil; Borkowska, Karolina; Polakowska, Anna; Pyzik, Alicja; Mróz, Oliwia; Domański, Andrzej; Domańska, Julia; Hornig, Nadia (Quality in Sport, 2026)
Background. Scheuermann disease is a developmental spinal pathology, typically manifesting during adolescence, characterized by thoracic or thoracolumbar hyperkyphosis. While many cases remain asymptomatic, progressive spinal deformity can lead to chronic back pain, neurological issues, restrictive respiratory impairment, and significant psychosocial distress. Aim. The primary objective of this literature review is to comprehensively present the available conservative and surgical treatment modalities for patients diagnosed with Scheuermann’s disease and to analyze the complex challenges associated with selecting the appropriate therapeutic strategy. Material and methods. A literature search was conducted across databases including PubMed, Scopus, and Web of Science to identify relevant studies. This primary electronic search was additionally supplemented by a manual search of reference lists to ensure comprehensive coverage of the topic. Results. Conservative protocols integrating physiotherapy and spinal orthoses yield statistically significant vertebral remodeling in skeletally immature cohorts with mild to moderate curves. Conversely, operative interventions, primarily exclusive posterior or combined anterior and posterior fusions, are generally considered for rigid deformities exceeding 70 to 75 degrees. Further clinical parameters substantiating the necessity for surgical correction include intractable back pain, concurrent neurological symptoms, restrictive pulmonary impairment, documented continuous progression of the deformity, and profound psychosocial distress arising from diminished self-esteem. Conclusion. Conservative management remains the optimal initial modality, particularly during the active growth period, while surgical intervention is warranted for patients with severe deformity progression, debilitating somatic symptoms, or significant aesthetic concerns that impair their quality of life.